THE IMPACT OF THE BANK DEPOSIT INSURANCE SYSTEM IN CAPITAL ADEQUACY AND PROFITABILITY INDICATORS FOR THE IRAQI BANKING SECTOR AND COMPARISON WITH THE JORDANIAN BANKING SECTOR (American Journal of Business Management, Economics and Banking, 2023)
The aims of research to determine the extent impact of the banking deposit Insurance system that measured by deposit guarantee fees percentage in the Iraqi banking sector on two indicators, capital adequacy and bank profitability, and compare the same effect with the Jordanian banking sector. Accordingly, the research hypothesis was tested after selecting 10 private commercial banks, (5) of them are Iraqi listed in the Iraqi Deposit Insurance Institution and (5 others) from the Jordanian banking sector and listed in the Jordanian Deposit Insurance Institution for the period (2018-2021), and based on the EVIEWS13 statistical program, the researcher reached the conclusion that the deposit protection system does not affect on capital adequacy, nor does it affect bank profitability, and in both of the Iraqi and Jordanian sectors, the Deposit Insurance Institution more reflection on the individual dealers than on the performance of the banks themselves.